Immunoglobulin and haematocrit values of dental pulp showing hyperaemia and acute serious pulpitis. - (:unkn) unknown (My University, 1990)
In this study, we examined how the pulpal immune systems differ in children who suffer from hyperaemia and acute serous pulpitis. The Radial Immune Diffusion (RID) method was used to measure the IgA, IgG and IgM levels in pulpal blood in hyperaemia and acute serous pulpitis cases. The patient's own peripheral blood was used as the control group. The peripheral blood was taken with a capillary tube from the finger tip. The immunoglobulins and the Htc values of the blood were measured by the radial immune diffusion method. In our research, the immunoglobulin and hematocrit values of the blood (pulpal and peripheral) of 39 patients between the ages 6 to 13 years were measured. No significant difference was found between the IgA, IgG and IgM levels of pulpal and peripheral blood in hyperaemia and acute serous pulpitis cases. In the same patients, a significant difference was noted between the Htc values of the pulpal and peripheral blood.